Morphological similarities and differences of young players from selected sport team games - Jarosław Domaradzki; Sebastian Chmielewski; Dawid Koźlenia (Kazimierz Wielki University, 2019)
Introduction: Body physique is an important determinant of sports success. Knowledge in this area enables the effective selection of players for various sports disciplines. Aim: Using a multidimensional perspective, to determine the degree of variation in the body physique of athletes from four sports disciplines: American football, football, volleyball and handball. Materials and methods: The research was carried out in 2017 in sport clubs operating in the Lower Silesia Voivodship. The research group consisted of 125 male players, with a mean age of 16.27 years. They represented 4 sports disciplines and included 22 American football players, 30 football players, 49 handball players and 24 volleyball players. In the analysis, the measurements of height and weight were used as well as the Body Max Index, calculated with the following formula: body weight [kg]/body height [m]2 Results: The American football players had the highest body weight and the highest BMI. The handball and volleyball players were the tallest. The football players were characterised by the lowest body weight. Conclusions: Each of the analysed sports disciplines prefers players with a different body physique. Nevertheless, a greater similarity between the handball and volleyball players can be observed. American football players are more different morphologically, whereas football players are the least similar to the players from the other disciplines. The results of the study will facilitate both players' and coaches' decision-making process regarding the change of the sports discipline and the choice of a new one, if such need arises.